Experimental investigation of the effect of functionalized graphene on the creep behavior of epoxy - Bakbak, Okan; Colak, Ozgen (SAGE PUBLICATIONS LTD, 2024)
The objective of the current work was to investigate the creep behavior of functionalized graphene (f-GNF)-epoxy nanocomposite. Time and temperature-dependent mechanical behaviors were investigated by performing creep tests at three different stress levels and two different temperatures. Graphene produced by the electric arc discharge method was functionalized with Triton X-100 by a non-covalent method. Then, f-GNF-epoxy nanocomposites are produced by using the Three Roll Milling (3RM) method to eliminate nanofiller agglomeration. By performing quasi-static compression tests, stress levels for creep tests are determined as 50, 100, and 200 MPa to guarantee the viscoelastic deformation regime, around yield, and the viscoplastic deformation regime, respectively. The results indicate significant creep resistance in the nanocomposite with 0.1 wt% f-GNF. Depending on temperature and stress level, the effect of f-GNF is more pronounced at higher stresses and temperatures. f-GNFs have a significant effect on inhibiting the mobility of polymer chains, resulting improvements in the creep modulus. This indicates that thermally activated processes controlling the creep rate are in part inhibited by the presence of f-GNF. In the creep tests carried out for 2 h, a maximum improvement of 85% was observed in the creep modulus of epoxy-nanocomposite compared to pure epoxy at room temperature.
Keywords: Creep; graphene; nanocomposite; temperature-dependent behavior; MECHANICAL-PROPERTIES; THERMAL-CONDUCTIVITY; CARBON NANOTUBES; COMPOSITES; NANOPLATELETS; NANOCOMPOSITES; DISPERSION; INTERFACE; RECOVERY; Materials Science; Polymer Science